Green Economy from a Regional Perspective - a Polish Case Study - Jędrzejczak-Gas, Janina; Barska, Anetta; Wyrwa, Joanna; Nowak, Leopold (European Journal of Sustainable Development, 2024)
The article presents the elaboration and specification of the green economy concept, where resource scarcity, global climate change and environmental degradation are paving a new path towards sustainable development. The article addresses the issue of implementing the principles of green economy at the regional level. The implementation of a green economy at a regional level provides an excellent space for scientific deliberations. The aim of the research is to identify and assess the level of regional disparities in green economy development across Polish regions using a synthetic measure. The basis for the analysis was a set of substantively and statistically analyzed diagnostic variables from the years 2012-2022. The synthetic indicator of the green economy was calculated for every Polish region (NUTS 2) and the regions were ranked based on their score from highest to lowest. As a result of the analysis, the regional polarization and the ordering of regions in Poland in terms of the synthetic metric - green economy development - were discussed. Keywords: green economy, green growth, sustainable development, taxonomic methods.